PENGARUH KONDISI KEUANGAN, PERTUMBUHAN PERUSAHAAN DAN OPINI AUDIT MODIFIKASI GOING CONCERN TAHUN SEBELUMNYA TERHADAP PENERIMAAN OPINI AUDIT MODIFIKASI GOING CONCERN - Prismawardani, Ika; Pratomo, Dudi (Kiat Bisnis, 2014)
This research aims to analyze financial condition, corporate growth and going concern modification audit opinion of prior year toward acceptance of going concern modification audit opinion. The population in this research is manufacturing companies listed at Indonesia Stock Exchange from 2008-2012. The sampling was conducted by purposive sampling method. Data were analyzed by logistic regression analysis. The result shows that financial condition and prior year going concern modification audit opinion are significantly affect the acceptance of going concern modification audit opinion. In the contrary, corporate growth doesnât have affect on the acceptance of going concern modification audit opinion..Keywords : going concern modification audit opinion, financial condition, corporate growth